SMART GOVERNANCE: PEMANFAATAN TEKNOLOGI IOT DALAM PENGELOLAAN KOTA PINTAR - Jackson Yumame (CV. Adiba Aisha Amira, 2025)
Smart Governance through the utilisation of IoT (Internet of Things) technology is an innovative step in smart city management, aiming to improve service efficiency and quality of life for the community. IoT enables real-time data integration for the optimisation of city systems such as transportation, waste management, and environmental monitoring. Although promising, this implementation faces significant challenges including the cost of infrastructure development, data security and privacy, and the need for device interoperability. The successful implementation of Smart Governance depends on close collaboration between the government, the private sector, and the community. With strategic planning, continuous investment, and community education, the use of IoT technology in smart cities can provide great benefits and sustainability for city residents.